A Novel Method to Calculate Solar UV Exposure Relevant to Vitamin D Production in Humans. (27th May 2013) - Seckmeyer, Gunther; Schrempf, Michael; Wieczorek, Anna; Riechelmann, Stefan; Graw, Kathrin; Seckmeyer, Stefan; Zankl, Maria
Abstract We present a novel method to calculate vitamin D3–weighted exposure by integrating the incident solar spectral radiance over all relevant parts of the human body. Earlier investigations are based on the irradiance on surfaces, whereas our calculated exposure of a voxel model of a human takes into account the complex geometry of the radiation field. Assuming that sufficient vitamin D3 (1000 international units) can be produced within the human body in one minute for a completely uncovered body in vertical posture in summer at midlatitudes (e.g. Rome, June 21, noon, UV index of 10), we calculate the exposure times needed in other situations or seasons to gain enough vitamin D3. Our calculations show that the UV index is not a good indicator for the exposure which depends on the orientation of the body (e.g. vertical (standing) or horizontal (lying down) posture). Without clothing the exposure is dominated by diffuse sky radiation and it is nearly irrelevant how the body in vertical posture is oriented toward the sun. At the winter solstice (December 21, noon, cloudy) at least in central Europe sufficient vitamin D3 cannot be obtained with realistic clothing, even if the exposure were extended to all daylight hours.